No evidence for an effect of DNA methylation on multiple sclerosis severity at HLA-DRB1*15 or HLA-DRB5. - Handel, A; De Luca, G; Morahan, J; Handunnetthi, L; Sadovnick, A; Ebers, G; Ramagopalan, S (2010)
Multiple sclerosis (MS) is a complex neurological disease with huge variability in disease outcome. The majority of MS genetic susceptibility is determined by major histocompatibility complex (MHC) alleles, in particular haplotypes carrying HLA-DRB1*1501. HLA-DRB1*1501 also affects the clinical outcome of the disease and animal research has suggested that HLA-DRB5 interacts with HLA-DRB1*1501 to influence disease severity. We used an extremes-of-outcome design with 48 benign and 20 malignant MS patients to assess whether or not DNA methylation at HLA-DRB1*1501 and/or HLA-DRB5 also contributes to MS phenotypic heterogeneity. We found no significant effect of DNA methylation across HLA-DRB1*1501 and HLA-DRB5 on severity, although we cannot rule out time- or tissue-specific effects of DNA methylation.